2022
DOI: 10.1177/15910199221135289
|View full text |Cite
|
Sign up to set email alerts
|

Early neurological deterioration as a predictor of outcomes after endovascular thrombectomy for stroke: A systematic review and meta-analysis

Abstract: Background Early neurological deterioration (END) is a potential predictor for 90-day outcomes following mechanical thrombectomy for acute ischemic stroke (AIS). We performed a systematic review and meta-analysis to better understand whether END can be used as a surrogate for long-term outcomes. Methods Following the PRISMA guidelines, a systematic literature review of the English language literature was conducted using PubMed, MEDLINE, and Embase. END definition was cataloged for each included study. Outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Numerous studies demonstrated a significant correlation between END and unfavorable functional long-term outcomes. 7 , 8 , 10 , 11 However research on END unexplained with respect to long-term outcomes remains scarce. 9 In line with the aforementioned study, our work reveals a significant association between END unexplained and unfavorable functional outcomes at 90 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies demonstrated a significant correlation between END and unfavorable functional long-term outcomes. 7 , 8 , 10 , 11 However research on END unexplained with respect to long-term outcomes remains scarce. 9 In line with the aforementioned study, our work reveals a significant association between END unexplained and unfavorable functional outcomes at 90 days.…”
Section: Discussionmentioning
confidence: 99%
“… 4 6 Previous studies observed a strong association between END and unfavorable long-term functional outcomes in AIS-LVO patients. 7 10 Evident causes of END include the presence of reperfusion hemorrhage, unsuccessful recanalization, embolization in new vascular territories, early recurrent ischemic stroke and malignant edema. 11 , 12 The pathophysiology, risk factors and treatment strategies of END including these causes have been discussed in the literature.…”
Section: Introductionmentioning
confidence: 99%